2012
DOI: 10.1037/a0027339
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in the multisensory temporal binding window predict susceptibility to audiovisual illusions.

Abstract: Human multisensory systems are known to bind inputs from the different sensory modalities into a unified percept, a process that leads to measurable behavioral benefits. This integrative process can be observed through multisensory illusions, including the McGurk effect and the sound-induced flash illusion, both of which demonstrate the ability of one sensory modality to modulate perception in a second modality. Such multisensory integration is highly dependent upon the temporal relationship of the different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
256
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 235 publications
(285 citation statements)
references
References 99 publications
24
256
5
Order By: Relevance
“…Thus, accounting for the differences in propagation times of the auditory and visual signals, the brain assesses audiovisual temporal structure in relation to this window, and thus makes a probabilistic judgment as to whether the stimuli belong together or not. These data strongly argue for the TBW as a measure of temporal acuity and strength of multisensory integration, and indeed it has been shown that the width of this window appears to be correlated with the magnitude of the binding process, with those with smaller windows having larger indices of integration 18,27 . In addition to be a probabilistic construct across individuals, the TBW is also very much dependent on stimulus and task.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Thus, accounting for the differences in propagation times of the auditory and visual signals, the brain assesses audiovisual temporal structure in relation to this window, and thus makes a probabilistic judgment as to whether the stimuli belong together or not. These data strongly argue for the TBW as a measure of temporal acuity and strength of multisensory integration, and indeed it has been shown that the width of this window appears to be correlated with the magnitude of the binding process, with those with smaller windows having larger indices of integration 18,27 . In addition to be a probabilistic construct across individuals, the TBW is also very much dependent on stimulus and task.…”
Section: Discussionmentioning
confidence: 97%
“…As an example of the utility of this battery, individual differences in temporal processing (such as the width of the TBW) can be correlated with performance differences on a perceptual task like the McGurk illusion ( Figure 3B). Several studies have observed a link between temporal acuity in the SJ task and perceptual differences in speech perception in the McGurk task and other measures of multisensory integration 18,27 . Because of the variability of responses for the same stimulus both within individual subjects and across subjects in a group, responses are shown as the percent of trials that were perceived as each phoneme.…”
Section: Representative Resultsmentioning
confidence: 99%
See 3 more Smart Citations